PENGARUH TINGKAT INFLASI, DEBT TO EQUITY RATIO, LIKUIDITAS OBLIGASI DAN RATING OBLIGASI TERHADAP YIELD OBLIGASI KORORASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009 – 2012 - Oktavian, Oky; ', Haryetti; ', Sjahruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine empirically the effect of the inflation rate, debt to equity ratio, the liquidity of the bond, and the bond rating of the ield of corporate bonds and relationship between the independent variables on the dependent variable. The sample was the company that issued corporate bonds from 2009 until the end of 2012 were listed in the Indonesia Stock Exchange Samples were selected using purposive sampling method and obtained a sample of 30 companies. Hypothesis testing was performed using multiple regression analysis. The research proves that the bond ratings affect the yield to maturity, while the rate of inflation, debt to equity ratio, the liquidity of bonds and bond rating has no effect on bond yields. Thus, investing in bonds Bondholder need to pay attention to bond ratings.Keywords: Inflation, debt to equity ratio, the liquidity of bonds, bond ratings, yield corporate bonds.